The role of chemotherapy in soft tissue sarcomas - Jassem, Jacek; Wełnicka-Jaśkiewicz, Marzena (Contemporary Oncology/Współczesna Onkologia, 1999)
Soft tissue sarcomas is highly heterogeneous group of neoplasms with different level of chemosensitivity. The rationale for chemotherapy trials of these tumours is based on unsatisfactory results of local treatment and a high rate of hematogenic spread. The role of chemotherapy in adult patients remains controversial. Its use as an adjunct to local therapies results in prolonged time to relapse but does not significantly influence overall survival. The results of randomised trials performed until now should, however, be interpreted cautiously due to methodological flaws and small numbers of patients. Thus, further studies are warranted, particularly in high-risk patients (large or poorly differentiated tumors). In advanced disease the role of chemotherapy is exclusively palliative. Response can be achieved in a proportion of patients but prolongation of survival is doubtful.